2013
DOI: 10.1074/jbc.m112.433243
|View full text |Cite
|
Sign up to set email alerts
|

Several Phenylalanine-Glycine Motives in the Nucleoporin Nup214 Are Essential for Binding of the Nuclear Export Receptor CRM1

Abstract: Background: Nup214 interacts with the nuclear export receptor CRM1 and promotes export of certain cargos. Results: Several FG motives in the C-terminal region participate in CRM1 binding. Conclusion: CRM1, like other transport receptors, makes multiple contacts to nucleoporins. Significance: Elucidation of the details of nucleoporin-receptor interactions is essential for our understanding of the transition process of transport complexes through the nuclear pore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 60 publications
4
38
0
Order By: Relevance
“…3B). This indicated that the C-terminal region of Nup214 can function as a dominant negative mutant of endogenous Nup214, as reported previously (39). From these observations, we conclude that SET-Nup214 and DEK-Nup214 change the subcellular localizations of endogenous proteins harboring NES by inhibiting the function of endogenous Nup214.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…3B). This indicated that the C-terminal region of Nup214 can function as a dominant negative mutant of endogenous Nup214, as reported previously (39). From these observations, we conclude that SET-Nup214 and DEK-Nup214 change the subcellular localizations of endogenous proteins harboring NES by inhibiting the function of endogenous Nup214.…”
Section: Resultssupporting
confidence: 61%
“…In addition, in cells expressing DEK-Nup214, we could not find clear accumulation of NXF1 at the sites where DEK-Nup214 was accumulated. It was reported previously that the FG repeat region of Nup214 plays crucial roles in binding with NTRs (31,32,39,42). Therefore, we next examined the importance of the FG repeat region of the fusion proteins for the changes in the localization of XPO1 and NFX1 by using the deletion mutant of SET-Nup214 termed SET-Nup214(1637), which lacks the FG repeat region of SET-Nup214.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, there may be some redundancy in the roles of FG-Nups, but this redundancy may be necessary, for example, to guarantee that some FG-Nups can bind critical NTRs that carry crucial macromolecules cross the NPC in any situation. [35][36][37] Another evolutionary feature present in FG-Nups in higher eukaryotic cells is the post-transcription modification. For example, in metazoans, FG-Nups are often glycosylated via O-linked-N-acetyL-glucosamine transferase, but functions of this modification in cells remain unknown.…”
Section: Fg-nups In Yeast Cellsmentioning
confidence: 99%
“…6 It is also possible that, at least in some cases, a cargo-bound NTR that binds to multiple FG-Nups would enhance their avidity of the interactions, which is likely necessary for their ultimate transporting success. 36,58 On the other hand, multiple FG-repeats of each FG-Nup could cope to ease the heavy transporting tasks and also provide cells with some necessary and some redundant functions. Sequence alignment of FG-Nups from 4 species of yeast identified small stretches of conserved AAs (6-11 AAs) (called 'islands') among divergent FG-domains.…”
Section: Multiple Binding Sites Of Ntrs For Fg-nupsmentioning
confidence: 99%